LEADERSHIP AND CHALLENGES OF BUREAUCRACY PATHOLOGY - Wasil Mubarok (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2023)
In the context of leadership styles , emphasis is placed on the importance of leaders having a deep understanding of organizational dynamics and choosing an appropriate leadership style. The article outlines that a democratic leadership style , by involving subordinates in decision making, can reduce resistance to change and create a greater sense of ownership among subordinates. This article discusses the use of secondary data, especially from scientific articles, as a source of information to strengthen arguments and findings in research. Secondary data includes research results, analysis, or findings that have been published by researchers or experts in related fields. The author emphasizes that the use of secondary data can provide a strong empirical basis, increase credibility, and support arguments or hypotheses in the article. Next, this article investigates various leadership styles and their impact on influence, motivation, and direction on team members. Each leadership style has advantages and disadvantages, with the caveat that leaders must choose a style that suits their bureaucratic context. Leaders are faced with opportunities to use leadership styles that can bring positive change, overcome bureaucratic pathologies, and improve organizational performance. In the context of leadership styles , emphasis is placed on the importance of leaders having a deep understanding of organizational dynamics and choosing an appropriate leadership style. The article outlines that a democratic leadership style , by involving subordinates in decision making, can reduce resistance to change and create a greater sense of ownership among subordinates. Finally, the article notes that leaders face threats to the effectiveness of their leadership styles , primarily from rigid policies and procedures and inflexible bureaucratic systems. These obstacles can hinder leaders' efforts to introduce innovation and improve organizational performance. Finally, the article notes that leaders face threats to the effectiveness of their leadership styles , primarily from rigid policies and procedures and inflexible bureaucratic systems. These obstacles can hinder leaders' efforts to introduce innovation and improve organizational performance.